2016
DOI: 10.1152/ajpheart.00464.2015
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and hemodynamic analysis of atherosclerotic progression in human carotid artery bifurcations

Abstract: analysis of atherosclerotic progression in human carotid artery bifurcations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 33 publications
(84 reference statements)
2
32
0
5
Order By: Relevance
“…[8][9][10][11][12][13][14][15][30][31][32][33][34][35][36] For instance, coronary CTA-based CFD models have been used to compute noninvasive FFR in CAD, allowing a considerable proportion of CAD patients to avoid the invasive FFR procedure, without increasing the risk of major adverse cardiovascular events. [8][9][10][11][12][13][14][15][30][31][32][33][34][35][36] For instance, coronary CTA-based CFD models have been used to compute noninvasive FFR in CAD, allowing a considerable proportion of CAD patients to avoid the invasive FFR procedure, without increasing the risk of major adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[8][9][10][11][12][13][14][15][30][31][32][33][34][35][36] For instance, coronary CTA-based CFD models have been used to compute noninvasive FFR in CAD, allowing a considerable proportion of CAD patients to avoid the invasive FFR procedure, without increasing the risk of major adverse cardiovascular events. [8][9][10][11][12][13][14][15][30][31][32][33][34][35][36] For instance, coronary CTA-based CFD models have been used to compute noninvasive FFR in CAD, allowing a considerable proportion of CAD patients to avoid the invasive FFR procedure, without increasing the risk of major adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][30][31][32][33][34][35][36] For instance, coronary CTA-based CFD models have been used to compute noninvasive FFR in CAD, allowing a considerable proportion of CAD patients to avoid the invasive FFR procedure, without increasing the risk of major adverse cardiovascular events. 30,34,35 Compared with extracranial arteries, however, hemodynamics in intracranial arteries are more difficult to assess with invasive imaging methods, due to the anatomic features of intracranial arteries (eg, small calibers, tortuosity, and deep locations of the arteries within the skull). 14 Moreover, CFD modeling methods have been used in studying the relationships between geometry, hemodynamic environment, and atherosclerosis at the carotid bifurcation in numerous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are various potential risk factors for the development of intracranial diseases, e.g., hypertension, smoking, hyperhomocysteinemia (HHcy), dyslipidemia, diabetes mellitus (Arbab-Zadeh and Fuster, 2015;Toutouzas et al, 2015), and biomechanical stresses (Chatzizisis et al, 2008;Seneviratne et al, 2013;Toutouzas et al, 2015;Thondapu et al, 2016). Previous studies have shown that a mild stenosis significantly increased the time-averaged wall shear stress (TAWSS) and decreased the oscillatory shear index (OSI) to result in a more uniform distribution of hemodynamic parameters inside the stenosis (Huo et al, 2013a;Huang et al, 2016). The stenosis also created the disturbed flows distal to the stenosis.…”
Section: Introductionmentioning
confidence: 99%